Commitment in educational practice. Piero Bertolini's ideas on maladjustment and juvenile delinquency - Laura Cavana (University of Bologna, 2016)
The concept of intentional consciousness, taken by Piero Bertolini from Husserlian phenomenology, is central to his pedagogical perspective. It expresses the substantive way of our being-in-the-world, and affects the quality of the relationship we establish with it. This contribution begins with a reference to chapters II and III of L'esistere pedagogico, aiming to examine this concept; it then describes its application also to the field of re-education. This is because: a) from 1958 to 1968, the phenomenological approach allowed Bertolini to tackle the difficult reality of maladjustment and juvenile delinquency in "new" terms; b) today, Piero Bertolini's interpretations of "that" reality and consequently his practical proposals still constitute the most commonly adopted pedagogical reference; c) the commitment to re-education, which in chronological terms concerned the first part of his professional life, allowed Bertolini, right from the outset, to characterise his pedagogy as the outcome of a continuous interaction between theory and practice.